Proteases in Doping control analysis - Thevis, M.; Maurer, J.; Kohler, M.; Geyer, H.; Schänzer, W. (International Journal of Sports Medicine, 2007)
Urine manipulation in sports drug testing has become a serious problem for doping control laboratories, and recent scandals in elite endurance sports have revealed the problem of urine manipulation presumably using proteases, which will impede the detection of drugs such as erythropoietin (EPO) or other peptide hormones. Using commonly accepted analytical strategies, a protocol was developed enabling the determination of elevated protease activities in doping control specimens followed by the visualization of protein degradation and identification of proteases such as chymotrypsin, trypsin and papain. Therefore, protease detection kits based on fluorescein isothiocyanate-labeled casein were employed, and protease concentrations greater than 15 µg/mL of urine entailed subsequent 1-dimensional gel electrophoretic visualization of urinary proteins. The presence of 20 µg of proteases per mL of urine caused a complete degradation of proteins usually observed in urinary matrices ("trace of burning"), while respective proteases were still detected in spiked urine samples after 10 days of storage at + 4 and - 20 °C. Identification of target proteases at respective molecular weights was accomplished using bottom-up sequencing approaches based on in-gel digestion of separated enzymes followed by capillary liquid chromatography - Orbitrap tandem mass spectrometry.